La formación del Contrato Mercantil - Zegarra Mulánovich, Álvaro (Revista de Derecho, 2019)
This paper studies the impact that commerciality has on the construction and effectivenessof the rules governing the formation of contracts, most of them containedin the Civil Code.
Keywords: Formation of contract; offer and acceptance; public offer; binding advertising statements; contracting at a distance; auction